Application of E-Learning Learning Media with Schoology on Character Education - TM Sahudra; N. Nurmasytah; N. Nursamsu (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
Strengthening Character Education (PPK) is an attempt by the government to improve the national education system. Character is the main foundation that is most important for achieving educational goals. Improving the education system is also done by improving the curriculum used by schools. The 2013 curriculum is currently in force by making changes to the content standards and assessment standards. Schoology is a site that combines social networking and LMS, so that with Schoology, we can interact socially while learning. The research objective is to applymedia E-Learning learning with Schoology towards strengthening character education (PPK). The research method used is quantitative experimental research. The sample in this study consisted of 30 students of SMP Negeri 1 Kota Langsa. Data collection is done by measuring character education. The results of this study are 66.93% religious character, social care character value 71.20, discipline character with 74.93 value and responsibility character value 72.53. The conclusion of this study is very high religious character.